Known Knowns and Known Unknowns: Epiphanius of Salamis and the Limits of Heresiology*. (6th January 2016) - Berzon, Todd S.
Abstract : In this essay, I explore the conceptual and discursive ruminations of Epiphanius of Salamis as he struggles in his Panarion to survey and manage the ever-expanding heretical world. Instead of reading this heresiological treatise as an attestation of theological, ecclesiastical, and intellectual authority established through totalizing discourse, I approach it as an expression of ancient ethnographic writing and the ethnographic disposition, an authorial orientation toward the world that describes, regulates, and classifies peoples with both macroscopic and microscopic knowledge. Ethnography in the ancient world was a process of writing the world's people into texts, describing and classifying specific cultures and customs through the lens of the ethnographer's own culturally situated perspective. Frequently, the ethnographer used his text to elaborate his assumptions about the origins of human diversity. Customs and habits were explained as the products of larger macroscopic forces such as astrology, genealogy, climatology, universal history, and myth. In the process of translating the world into texts, ethnographic inquiry forced authors to confront their capacity to comprehend the world around them and ultimately to come to terms with the full scope of human diversity. I argue that reading the Panarion as a manifestation of Christian ethnography usefully foregrounds an intractable tension between knowledge (known knowns) and self-conscious ignorance (known unknowns) about the depths of human heterogeneity: ethnography is as much an illustration of incomprehension as it is a repository of erudition, mastery, and discovery.